Consumer acceptance of plant-forward recipes in a natural consumption setting. (March 2021) - Spencer, Molly; Rowe, Steven; Bonnell, Carrie; Dalton, Pamela
Highlights: Consumer acceptability of plant-forward dishes was studied in a restaurant setting. The plant-forward dishes were as acceptable as their conventional counterparts. The type of main course had a significant impact on subsequent dessert choice. Abstract: There is a push for Western diets to be more plant-based due to the negative environmental, food system, and health implications associated with the conventional meat-centric diet. One plant-forward strategy to maintain consumer acceptability is to modify dishes and desserts to have proportionately more plant-based ingredients and fewer animal-based ingredients. We tested four versions of a main course (bowl) in a natural consumption dining setting (n = 144) with a between-groups design (conventional spicy, conventional mild, plant-forward spicy and plant-forward mild), with two versions of a dessert afterwards. Here we show that plant-forward main course dishes and desserts are just as acceptable, satiating, and satisfying as conventional bowls. This demonstrates that these recipe modifications are a successful strategy in the plant-based diet movement. Of the two dessert options, more consumers selected the conventional dessert after consuming the plant-forward bowls, and more consumers selected the plant-forward dessert (increased fruit/reduced cake) after consuming the conventional bowls. This finding warrants further investigation.